The challenge of managing soil functions at multiple scales: An optimisation study of the synergistic and antagonistic trade-offs between soil functions in Ireland - Valujeva, Kristine; O’Sullivan, Lilian; Gutzler, Carsten; Fealy, Reamonn; Schulte, Rogier P.O. (Land use policy, 2016)
Recent forecasts show a need to increase agricultural production globally by 60% from 2005 to 2050, in order to meet a rising demand from a growing population. This poses challenges for scientists and policy makers to formulate solutions on how to increase food production and simultaneously meet environmental targets such as the conservation and protection of water, the conservation of biodiversity, and the mitigation of greenhouse gas emissions. As soil and land are subject to growing pressure to meet both agronomic and environmental targets, there is an urgent need to understand to what extent these diverging targets can be met simultaneously. Previously, the concept of Functional Land Management (FLM) was developed as a framework for managing the multifunctionality of land. In this paper, we deploy and evaluate the concept of FLM, using a real case-study of Irish agriculture. We investigate a number of scenarios, encompassing combinations of intensification, expansion and land drainage, for managing three soil functions, namely primary productivity, water purification and carbon sequestration. We use proxy-indicators (milk production, nitrate concentrations and area of new afforestation) to quantify the ‘supply’ of these three soil functions, and identify the relevant policy targets to frame the ‘demand’ for these soil functions. Specifically, this paper assesses how soil management and land use management interact in meeting these multiple targets simultaneously, by employing a non-spatial land use model for livestock production in Ireland that assesses the supply of soil functions for contrasting soil drainage and land use categories. Our results show that, in principle, it is possible to manage these three soil functions to meet both agronomic and environmental objectives, but as we add more soil functions, the management requirements become increasingly complex. In theory, an expansion scenario could meet all of the objectives simultaneously. However, this scenario is highly unlikely to materialise due to farm fragmentation, low land mobility rates and the challenging afforestation rates required for achieving the greenhouse gas reduction targets. In the absence of targeted policy interventions, an unmanaged combination of scenarios is more likely to emerge. The challenge for policy formation on future land use is how to move from an unmanaged combination scenario towards a managed combination scenario, in which the soil functions are purposefully managed to meet current and future agronomic and environmental targets, through a targeted combination of intensification, expansion and land drainage. Such purposeful management requires that the supply of each soil function is managed at the spatial scale at which the corresponding demand manifests itself. This spatial scale may differ between the soil functions, and may range from farm scale to national scale. Finally, our research identifies the need for future research to also consider and address the misalignment of temporal scales between the supply and demand of soil functions.